Analisis Penerapan Prinsip Prinsip Good Governance Dalam Meningkatkan Kualitas Pelayanan Pajak Pada Kantor Pelayanan Pajak Madya Kota Bekasi - Yani Yani; Dwikora Harjo; Ria Meilye Yanti (Jurnal Ilmu Administrasi Publik, 2023)
Good governance has long been a dream for many people in Indonesia. Most of them envision that through the application of good governance, the quality of government can be improved. However, the phenomenon of public service by government bureaucracy still often presents issues, such as service officers refusing taxpayers who are not registered with the appropriate tax service office. The purpose of this research is to analyze the application of good governance principles to enhance the quality of tax services at the Tax Service Office of Madya Bekasi City. This study employs a qualitative approach with a descriptive method, and the research is conducted at the Tax Service Office of Madya Bekasi City. The results of this research illustrate that the application of good governance principles at the Tax Service Office of Madya Bekasi City has been implemented well and has contributed to the improvement of the quality of tax services. However, during the implementation of these principles, various obstacles were encountered, resulting in less satisfactory services provided by the Tax Service Office of Madya Bekasi City. These obstacles include frequent operational issues, changing regulations and policies, and a lack of awareness among taxpayers about these changes. Therefore, the Tax Service Office of Madya Bekasi City countinues to provide counselling through social media and conducts online tax classes to enhance knowledge in the field of taxation. By increasing taxpayers’ knowledge of tax regulations, it is hoped that the quality of tax services can be improved.